(untitled) (Research Nepal Journal of Development Studies, 2019)
Rural development is process of socio economic transformation of rural people by rural people. So as the rural people Baram community of Gorkha have initiated own development interventions on different sectors of local development. Rural development is a process of action with economic, political, cultural and social dimensions. To put it differently, agricultural development is a process whereby the farmers possess modern knowledge and information. It is imperative for the farmers to have and accept the necessary technologies, innovations and knowledge for the rural development. The objective of the study is to explore the rural development initiatives on Environment, Agriculture, Tourism, Innovation, Employment, Migration, and informal economy of Baram Community of Takukot Gorkha Nepal. Methodologically 10 households were surveyed as Household questionnaire survey (HS). Purposively 1 female and 4 male ward members were selected for focus group discussion (FGD) in ward office. One ward chairperson was invited for Key Informant’s Interview (KII). In conclusion Baram community is one of the dignified community of Nepal. Economically and socially their living standard is below the satisfactory line. They are marginalized people but laborious and active in rural development activities in rural municipalities. Baram communities are highly active in environment conservation, modern agriculture, rural innovation, tourism, employment generation and other informal economies.